Recent Advances in Botulinum Neurotoxin Inhibitor Development - Kiris, Erkan; C. Burnett, James; D. Kane, Christopher; Bavari, Sina (Current Topics in Medicinal Chemistry, 2014)
Botulinum neurotoxins (BoNTs) are endopeptidases that target motor neurons and block acetylcholine neurotransmitter release. This action results in the muscle paralysis that defines the disease botulism. To date, there are no FDA-approved therapeutics to treat BoNT-mediated paralysis after intoxication of the motor neuron. Importantly, the rationale for pursuing treatments to counter these toxins is driven by their potential misuse. Current drug discovery efforts have mainly focused on small molecules, peptides, and peptidomimetics that can directly and competitively inhibit BoNT light chain proteolytic activity. Although this is a rational approach, direct inhibition of the Zn2+ metalloprotease activity has been elusive as demonstrated by the dearth of candidates undergoing clinical evaluation. Therefore, broadening the scope of viable targets beyond that of active site protease inhibitors represents an additional strategy that could move the field closer to the clinic. Here we review the rationale, and discuss the outcomes of earlier approaches and highlight potential new targets for BoNT inhibition. These include BoNT uptake and processing inhibitors, enzymatic inhibitors, and modulators of neuronal processes associated with toxin clearance, neurotransmitter potentiation, and other pathways geared towards neuronal recovery and repair.
Keywords: botulism